Análise espacial e quimiométrica da distribuição de espécies metálicas em solos alagáveis e não alagáveis da Bacia do Médio Rio Negro, Amazônia - Cordovil, Mirela Cristina De Oliveira [UNESP]; Mendonça, André Gustavo Ribeiro; Botero, Wander Gustavo; Santos, Ademir dos [UNESP]; Rocha, Julio Cesar [UNESP]; Mello, Kaline De; Toppa, Rogério Hartung; Oliveira, Luciana Camargo De (Sociedade Brasileira de Química, 2014)
This study used chemometric tools and a Geographic Information System (GIS) to determine the influence of organic matter and anthropogenic activity on the distribution of metal species between two major communities of the Middle Negro River Basin-AM. Higher concentrations of metal species were determined in flooded regions. The chemometric analysis showed the affinity of organic matter for potentially toxic metals, indicating its selectivity. GIS spatial analysis has shown that proximity to urban areas is a variable that is likely to influence the pattern of concentration of organic matter, and consequently the distribution of metal species between flooded and non-flooded areas.
Spatial and chemometric analysis of the distribution of metal species in flooded and non-flooded soils from the Middle Negro River Basin, Amazon
Keywords: soils; metals; chemometric; Amazon